Захист інформації в системах електронного документообігу - Санжарова, А. К. (ХНУРЕ, 2024)
The work examines potential threats and the most common ways of information leakage from electronic document management systems, analyzes the main measures aimed at increasing data security, protecting confidential information and minimizing cyber threats.
Keywords: електронний документообіг; захист інформації